Synergistic Effects of Branched-chain Amino Acids and Phenylalanine Addition on Major Volatile Compounds in Wine during Alcoholic Fermentation - Wang, Y.-Q.; Ye, D.-Q.; Liu, P.-T.; Duan, L.-L.; Duan, C.-Q.; Yan, G.-L. (South African Journal of Enology and Viticulture, 2016)
The effects of adding branched-chain amino acids (BCAAs, including L-valine, L-leucine and L-isoleucine), L-phenylalanine and a mixture of them (BCAAs + Phe) on the fermentation profiles of wine yeast EC1118 and the production of volatile compounds were investigated in synthetic grape juice. The addition of selected amino acids had no considerable influence on the yeast growth and primary metabolites of the sugars. Adding BCAAs increased the production of higher alcohols, medium-chain fatty acids (MCFAs) and their corresponding ethyl esters. In comparison, adding Phe promoted the production of 2-phenylethanol, 2-phenylethyl acetate and ethyl esters of MCFAs. Nevertheless, the supplementation of BCAAs + Phe further heightened the production of MCFAs, acetate esters and ethyl esters of MCFAs compared to the single additions, but it attenuated the production of various higher alcohols (1-propanol, 2,3-butanediol and methionol) compared to the addition of BCAAs, and of 2-phenylethanol and 2-phenylethyl acetate contents compared to the Phe addition. These results suggest that adding BCAAs or Phe is an efficient way to adjust wine’s aromatic composition and complexity. Meanwhile, the combined addition of BCAAs + Phe could be a potential tool to further manipulate wine’s aromatic profile by accentuating or suppressing the formation of certain aroma compounds.